2012
DOI: 10.1038/ni.2301
|View full text |Cite
|
Sign up to set email alerts
|

Tespa1 is involved in late thymocyte development through the regulation of TCR-mediated signaling

Abstract: Signaling via the T cell antigen receptor (TCR) during the CD4(+)CD8(+) double-positive developmental stage determines thymocyte selection and lineage commitment. Here we describe a previously uncharacterized T cell-expressed protein, Tespa1, with critical functions during the positive selection of thymocytes. Tespa1(-/-) mice had fewer mature thymic CD4(+) and CD8(+) T cells, which reflected impaired thymocyte development. Tespa1 associated with the TCR signaling components PLC-γ1 and Grb2, and Tespa1 deficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
77
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(81 citation statements)
references
References 33 publications
4
77
0
Order By: Relevance
“…DN3 transition to DN4 and DP stage requires successful TCRβ gene rearrangements, namely V(D)J recombination, and β-selection (14). We found that Vβ11-Jβ2 and Vβ5-Jβ2 recombination was moderately impaired upon RhoA deletion, whereas Vβ8-Jβ2, Dβ2-Jβ2, Dβ2.1-Jβ2.7, and Dβ1.1-Jβ1.7 rearrangements were completely intact (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…DN3 transition to DN4 and DP stage requires successful TCRβ gene rearrangements, namely V(D)J recombination, and β-selection (14). We found that Vβ11-Jβ2 and Vβ5-Jβ2 recombination was moderately impaired upon RhoA deletion, whereas Vβ8-Jβ2, Dβ2-Jβ2, Dβ2.1-Jβ2.7, and Dβ1.1-Jβ1.7 rearrangements were completely intact (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…T cell development in thymus proceeds through a series of differentiation stages (14). The most immature populations in thymus comprise CD4 − CD8 − double-negative (DN) thymocytes.…”
Section: Introductionmentioning
confidence: 99%
“…However, recent investigations have indicated that more non-MHC genes may be associated with RA susceptibility, such as PTPN22, PADI4, TRAF1-C5, STAT4, and ARL15 [20][21][22][23][24][25][26][27]. In our previous work, we identified Tespa1 [7], a gene that interacted with the linker for activation of T cells (LAT) signalosome formed during TCR signaling, thus playing a key role in the regulation of T cell development. Liu et al's work indicated that the Tespa1 gene is not involved in the genetic predisposition to ankylosing spondylitis (AS) but may play an important role in the clinical characteristics of AS [11].…”
Section: Discussionmentioning
confidence: 99%
“…Our previous work demonstrated that a gene associated with immune responses, Tespa1, is a component of the T cell receptor (TCR) signalosome and is essential for T cell selection and maturation through the regulation of TCR signaling during T cell development [7]. Tespa1 also negatively regulates FcεRI-mediated signaling and the mast cell-mediated allergic response [8].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, studies with mice lacking TCR structural components (34,35) or downstream signaling molecules such as LCK (30), LAT (39), GRB2 (40), TESPA1 (41), and ITK (42) show severe defects in T cell development with significant immunodeficiency (reviewed in reference 43). LCK acts immediately downstream of the TCR, and upon its activation, it phosphorylates THEMIS (31)(32)(33).…”
Section: Discussionmentioning
confidence: 99%